Association between Heavy Metal Exposure and Parkinson's Disease: A Review of the Mechanisms Related to Oxidative Stress - Sarita Pyatha; Haesoo Kim; Daeun Lee; Kisok Kim (MDPI AG, 2022)
Parkinson's disease (PD) is a gradually progressing neurodegenerative condition that is marked by a loss of motor coordination along with non-motor features. Although the precise cause of PD has not been determined, the disease condition is mostly associated with the exposure to environmental toxins, such as metals, and their abnormal accumulation in the brain. Heavy metals, such as iron (Fe), mercury (Hg), manganese (Mn), copper (Cu), and lead (Pb), have been linked to PD and contribute to its progression. In addition, the interactions among the components of a metal mixture may result in synergistic toxicity. Numerous epidemiological studies have demonstrated a connection between PD and either single or mixed exposure to these heavy metals, which increase the prevalence of PD. Chronic exposure to heavy metals is related to the activation of proinflammatory cytokines resulting in neuronal loss through neuroinflammation. Similarly, metals disrupt redox homeostasis while inducing free radical production and decreasing antioxidant levels in the substantia nigra. Furthermore, these metals alter molecular processes and result in oxidative stress, DNA damage, mitochondrial dysfunction, and apoptosis, which can potentially trigger dopaminergic neurodegenerative disorders. This review focuses on the roles of Hg, Pb, Mn, Cu, and Fe in the development and progression of PD. Moreover, it explores the plausible roles of heavy metals in neurodegenerative mechanisms that facilitate the development of PD. A better understanding of the mechanisms underlying metal toxicities will enable the establishment of novel therapeutic approaches to prevent or cure PD.